Potter wasps of the genus Eumenes Latreille, 1802 (Hymenoptera: Vespidae: Eumeninae) from Vietnam, with description of a new species and key to species - Nguyen, Lien Thi Phuong (Zootaxa, 2015)
Seven species of the genus Eumenes Latreille, 1802 are recorded from Vietnam. A new species, E. gibbosus Nguyen, sp. nov. is described and figured. Eumenes atrophicus (Fabricius, 1798), E. inconspicuus Smith, 1858, E. labiatus sinicus Giordani Soika, 1941, and E. rubronotatus Pérez, 1905 are newly recorded from Vietnam. A key to species is given.